Divestiture as a new trend in the information age / Mohd Soffi Puteh - Puteh, Mohd Soffi (Universiti Teknologi MARA Cawangan Pahang, 2004)
The world has seen so many companies merging in their pursue of becoming the greatest in every sector of industries. Some of them have survived, and some have not. Most of the survived ones have undergone the opposite way of merging; called divestiture. Due to some factors such as financial, managerial and operational, these companies have split-off the ‘added-up’ part of them and focus on their core businesses. Realize it or not, this trend has been followed by some Malaysian companies in the era after the economic turmoil in 1997 such as Telekom Malaysia (TM) and Land and General (L&G). This paper discusses the types of divestiture as well as the reasons for divestiture.